(untitled) (Research, Society and Development, 2025)
Absenteeism among medical students is a frequent and multifactorial phenomenon with potential impacts on academic performance, professional development, and the ethical formation of future physicians. Objective: To identify, based on scientific literature, the main factors associated with absenteeism in medical school. Methods: An integrative review was conducted in the PubMed database in March 2025 using the MeSH terms “Absenteeism” AND “Students, Medical.” Original studies addressing the causes of absenteeism among medical students were included. Results: The primary factors associated with absenteeism were lack of interest in course content, ineffective teaching methods, preparation for other exams, health problems, long internship hours, substance use, and difficulties in communication with faculty. Conclusion: Absenteeism is a relevant educational challenge and requires institutional actions for its prevention. Strategies such as faculty development, active learning methodologies, psychopedagogical support, and curricular restructuring are essential to mitigate this phenomenon.